2021
DOI: 10.3390/jpm11111201
|View full text |Cite
|
Sign up to set email alerts
|

Innate-Immunity Genes in Obesity

Abstract: The main functions of adipose tissue are thought to be storage and mobilization of the body’s energy reserves, active and passive thermoregulation, participation in the spatial organization of internal organs, protection of the body from lipotoxicity, and ectopic lipid deposition. After the discovery of adipokines, the endocrine function was added to the above list, and after the identification of crosstalk between adipocytes and immune cells, an immune function was suggested. Nonetheless, it turned out that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 243 publications
(335 reference statements)
0
18
0
Order By: Relevance
“…Several studies revealed an association between obesity and the rs758747 T allele. 53 Furthermore, NLRC3 deficiency promotes cutaneous wound healing due to the inhibition of p53 signaling. 54 As p53 is also involved in vascular remodeling and atherosclerosis, 55 thus we speculate that NLRC3 alteration could have reversed the expression and phosphorylation of p53 that is usually observed in advanced atherosclerotic plaques 56 and therefore reduced restenosis susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed an association between obesity and the rs758747 T allele. 53 Furthermore, NLRC3 deficiency promotes cutaneous wound healing due to the inhibition of p53 signaling. 54 As p53 is also involved in vascular remodeling and atherosclerosis, 55 thus we speculate that NLRC3 alteration could have reversed the expression and phosphorylation of p53 that is usually observed in advanced atherosclerotic plaques 56 and therefore reduced restenosis susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is an inflammatory type of programmed cell death characterized by plasma membrane rupture, water influx, cellular swelling, osmotic lysis and release of proinflammatory cytokines into the extracellular space [ 49 ]. Studies show that, in obesity, the death of adipocytes is described as death similar to pyrosis [ 50 ], where infiltrated macrophages aggregate around each dead adipocyte creating a “crown-shaped” structure and this leads to low-grade chronic inflammation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…They may also have a reduced response to vaccinations [87] . Adipocytes are actively involved in the regulation of inflammation and immunity [88,89] .…”
Section: Obesitymentioning
confidence: 99%
“…A poor nutritional status resulting in under nutrition can impair immunity to an infection due to micronutrient deficiencies [125,126] . On the other hand, over nutrition induces low-grade chronic inflammation caused by excess adiposity [88,89] . The harmful effects of excess body weight on infectious diseases have been discussed under obesity.…”
Section: Dietmentioning
confidence: 99%